Omega-3 Fatty Acids and Cholesterol Have a Main Role in Antidepression Diet of Iranian Traditional Medicine - Mohammad Mahdi Ahmadian-Attari PharmD, PhD; Ahmad Ali Noorbala MD; Alireza Khoshdel MD; Mohammad Kamalinejad PhD; Arsia Taghva MD (SAGE Publishing, 2017)
Depression is one of the major health problems of our world. Recent studies have revealed the relationship between diet and depression. In Iranian traditional medicine, there is a therapeutic diet that is recommended in melancholic diseases like depression. One of the main components of this diet is meat. Meats are divided into 2 groups: recommended and abstinent. The aim of this study was to clarify the logic of this diet through comparing nutritional elements of the 2 groups with each other. For this purpose, prominent books on Iranian traditional medicine were searched for abstinent and recommended meats traditionally prescribed for depressed patients. The results of each group were compared with the other by using Mann-Whitney Test (SPSS version 16). The results showed that recommended meats contain higher amounts of polyunsaturated fatty acids ( P = .01) especially omega-3 ( P = .03). Both groups contain high amounts of cholesterol. Iranian traditional medicine recommends consumption of meats that contains cholesterol with omega-3 fatty acids in depression.